THE EFFECT OF INTELLECTUAL CAPITAL AND CORPORATE GOVERNANCE ON BANK’S FINANCIAL PERFORMANCE IN INDONESIA - Tia Rizna Pratiwi (International Conference On Law, Business and Governance (ICon-LBG), 2016)
This study aimed to examine the effect of intellectual capital and corporate governance on the performance of banks in Indonesia. Intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC), while corporate governance is measured using a composite score of self-assessment of banking corporate governance. The results of this study indicate that VACA and VAHU make positive effect on the performance of banks in Indonesia, which is proxied by the ROA and ROE. However, corporate governance is not proven to have a significant influence on the performance of banks in Indonesia. In addition, this study also conducts tests for each type of bank. The results show that the Islamic banking VACA proved to have a greater impact on ROE of banking.